PENGARUH LIFESTYLE DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN SEPEDA DI TENGAH MASA PANDEMI COVID-19 - Gerry Nugraha Pradhana; Jul Aidil Fadli (CV. Adiba Aisha Amira, 2024)
This study aims to determine the effect of Lifestyle and Word of Mouth on Bicycle Purchase Decisions in the Middle of the Covid-19 Pandemic. This type of research is qualitative which is quantified. The population in this study is the people who live in Kab. Tangerang as many as 100 respondents using purposive sampling technique. Data collection technique by distributing questionnaires through Google Form. Hypothesis testing in this study using Multiple Linear Regression analysis. Research subjects Kab. Tangerang. The results of this study indicate that the Lifestyle and Word Of Mouth variables partially and simultaneously have a significant and positive effect on the bicycle purchase decision variable. The existence of a significant influence on Purchase Decisions indicates that Lifestyle and Word Of Mouth are important things that must be considered by companies to improve comfort, safety and promotion in making a bicycle product.